The status of greenhouses utilization in Oyo State, Nigeria (2011)
The toll of climate change on the Nigerian agricultural system in recent times has resulted in the decline of agricultural production constituting a threat to food security. There is therefore an urgent need for strategies to reverse the situation and greenhouse farming is contemplated as a possible option. Towards the successful adoption of this strategy, a survey was conducted using Oyo State as a case study to establish the present status of the use of greenhouses in the region. A total of 114 greenhouses in six locations within the teaching and research institutions and primarily used for the purpose of research and as nurseries were identified. The materials used in the construction of various parts include welded mesh, aluminium, iron, glass sheet and polythene films. These greenhouses have been successfully used in the cultivation of sugarcane, sweet potato, Irish potatoes, onions, greenbean, carrot, cucumber, olive tree, citrus seedlings, seedlings of obeche and other hardwoods. Infrequent research activities have led to the abandonment of many greenhouses. Prohibitive cost of construction and maintenance has discouraged individuals from venturing into greenhouse farming. Based on the performance of the crops cultivated in these greenhouses, it is believed that whatever investment may be made in the erection of greenhouses, such could be recovered within a short period of time and hence the introduction of greenhouses for crop production as one of the many options of combating the negative effects of climate change in Nigeria is advocated. Towards this accomplishment, it is recommended that the existing greenhouses be effectively utilized, there should be public enlightenment on the potentials of greenhouses, there should be sourcing for local construction materials to reduce cost, interested individuals especially the youths should be trained on greenhouse construction and maintenance while government intervention is required.